An assessment of the influence of the urban environment on collembolan communities in soils using taxonomy- and trait-based approaches (Applied Soil Ecology, 2014)
In this study we investigated collembolan communities using both taxonomy- and trait-based approaches in order to determine: (1) which soil or leaf litter characteristics are the main agents of species distribution and functional trait distribution in collembolan communities, and (2) which functional traits are more prevalent in species tolerant to urban environments. To investigate this, soil and leaf litter were sampled in the urban area of Naples, Italy and the collembolan community was analyzed using taxonomic and functional approaches. The results indicated that collembolan density was negatively affected by site pollution, and that species richness, diversity and evenness were positively affected by the organic matter content of the soil. Folsomia lawrencei was the most abundant species in sites with high metal contamination and low soil organic matter content, whereas Mesaphorura sp. and Parisotoma notabilis were the most ubiquitous taxa overall. The main agents affecting the frequency of functional traits were metal contamination of soil and litter, soil organic matter content, leaf specific mass and thickness of the litter. The species most tolerant to urban environmental conditions were found to have small body size, jumping motion strategy, sexual reproduction and presence of pigmentation.

Collembola populations under sclerophyllous coppices in Provence (France): comparison between two types of vegetation, Quercus ilex L. and Quercus coccifera L. - Cortet, Jérôme; Poinsot-Balaguer, Nicole (Acta Oecologica, 1998)
A comparative analysis of soil Collembola using two types of sclerophyllous vegetation (Quercus ilex and Quercus cocc@ru) was performed at a calcareous site in Provence (France). Collembola populations were examined over a one-year period (1 I successive months) in three different soil layers. Although no statistically significant differences could be observed for Collembola abundance and diversity, multivariate analyses (FCA) differentiated the two coppices. Phenologies of some species showed specific responses to the microclimate induced by edaphic conditions. Even though the two coppices were sclerophyllous, the structure of each vegetation, the quantity and quality of litter, which were dif- ferent, could influence environmental conditions and thus the dynamics of collembolan populations.
Keywords: Collembola; litter decomposition; Phenology; Quercus coccifera; Quercus ilex

Collembola populations under sclerophyllous coppices in Provence (France): comparison between two types of vegetation, Quercus ilex L. and Quercus coccifera L. (Acta Oecologica, 1998)
A comparative analysis of soil Collembola using two types of sclerophyllous vegetation (Quercus ilex and Quercus cocc@ru) was performed at a calcareous site in Provence (France). Collembola populations were examined over a one-year period (1 I successive months) in three different soil layers. Although no statistically significant differences could be observed for Collembola abundance and diversity, multivariate analyses (FCA) differentiated the two coppices. Phenologies of some species showed specific responses to the microclimate induced by edaphic conditions. Even though the two coppices were sclerophyllous, the structure of each vegetation, the quantity and quality of litter, which were dif- ferent, could influence environmental conditions and thus the dynamics of collembolan populations.